2006
DOI: 10.1080/17453670610013312
|View full text |Cite
|
Sign up to set email alerts
|

Does estrogen alter the mechanical properties of the anterior cruciate ligament?: An experimental study in rabbits

Abstract: Our findings suggest that high SEL might be one of the factors in the multifactorial pathogenesis of ACL rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…In a rat osteoporosis model created by an ovariectomy, Yoshida et al subcutaneously injected estradiol into the experimental group and found that the ACL is ER-dependent and that estrogen may alter ligament tissue composition, especially in the proximal position (15). The amount of estrogen used in our study is based on the articles previously conducted using subcutaneous estrogen in rats and rabbits, and we adjusted the dosage via transformation formula considering the species, route of medication and body surface area (15,32). The amount of estrogen used in our study is based on the articles previously conducted using subcutaneous estrogen in rats and rabbits, and we adjusted the dosage via transformation formula considering the species, route of medication and body surface area (15,32).…”
Section: Discussionmentioning
confidence: 99%
“…In a rat osteoporosis model created by an ovariectomy, Yoshida et al subcutaneously injected estradiol into the experimental group and found that the ACL is ER-dependent and that estrogen may alter ligament tissue composition, especially in the proximal position (15). The amount of estrogen used in our study is based on the articles previously conducted using subcutaneous estrogen in rats and rabbits, and we adjusted the dosage via transformation formula considering the species, route of medication and body surface area (15,32). The amount of estrogen used in our study is based on the articles previously conducted using subcutaneous estrogen in rats and rabbits, and we adjusted the dosage via transformation formula considering the species, route of medication and body surface area (15,32).…”
Section: Discussionmentioning
confidence: 99%
“…Various factors, including skeletal maturity, aging, daily activity, exercise, sex, and hormonal factors, influence the properties of these tissues [13,14]. It is not known if estrogen affects tendons and ligaments [15][16][17]. Previous studies, however, indicate the presence of estrogen receptors (ER) in tendons and ligaments [18,19].…”
Section: Introductionmentioning
confidence: 96%
“…11,41 Because differences in ligament size may play a role in the strength of knee ligaments, several methods, including computer modeling, 11 measurement from magnetic resonance imaging, 41 and micrometers, 42 have been used to account for various ligament sizes when calculating tensile and mechanical properties. Although these methods have routinely been used on larger human ligaments, the small size and structure of the rat ACL makes similar methods difficult to employ.…”
Section: Discussionmentioning
confidence: 99%